Challenging the legitimacy of the law as a form of protection of the dignity of man and citizen - KONARSKI, MARCIN (Prawo Kanoniczne, 2017)
This article is about the behavior patterns that challenge the legitimacy of the law. e analysis focuses on the basic forms of questioning the le- gitimacy of such rights namely the right to resistance, civil disobedience and revolution. e considerations made in this article are designed to synthetic analysis of the issues related to the questioning of state power by the citizens. e questions which are the subject of the following scientic reection of an academic nature can be examined from the point of view of dierent branches of science. ey are intensely analyzed on the ground of philosophy of history, political and economic history, political science, and many others. What seems obvious, in this paper emphasis is put on the subject of study of the law. e rights to resistance, civil disobedience and revolution as forms of challenging the legitimacy of the law are insuciently elaborated on in the science of the law and constitute a research area which few representatives of jurisprudence have the courage to step into. Typically, the aforementioned issues are raised in the science of the constitutional law however in a clearly insucient way. For centuries, problems related to challenging the legitimacy of the law have been the subject of interest of the philosophy of the law and it is mainly there where we can nd both questions and answers related to the binding force of the law as a system of norms of behaviour of particular importance. e following considerations are aimed at indicating basic theses to be coped with by a modern researcher focused on these socio-legal phenomena. Secondly, the following scientic reections onto the forms of challenging the legitimacy of the law stimulate further research onto the area which should denitely be carried out due to its importance and nature, as well as meaning in the context of problems we face in modern times.